Digital Modulation Techniques. - Xiong, Fuqin (Artech House, 2006)
IEEE Communications called the first edition ''extremely useful likely to become a standard reference'' and engineers worldwide have agreed! This newly revised and expanded edition of an Artech House classic builds on its success as far and away the most comprehensive guide to digital modulation techniques used in communications today. It devotes five new chapters to orthogonal frequency division multiplexing (OFDM), the hottest new bandwidth-efficient technique, and includes new modulations for optical communications. It also adds a fast-access comparison of all modulation schemes that wi.